Analisis Kemampuan Metakognitif Siswa melalui Think-Aloud pada Materi Aritmatika Sosial - Rahmawati Dini Aprilia; Arjudin; Gilang Primajati (Mataram University, 2026)
Students’ metacognitive ability in solving social arithmetic problems is not always evident in written answers; therefore, a method is needed to reveal students’ thinking processes more clearly. This study aims to describe students’ metacognitive ability through the think-aloud method on social arithmetic material. This study employed a descriptive qualitative approach. The subjects were six Grade VII students of MTs Asy-Syafi’iyah Bendung representing high, medium, and low mathematical ability categories, with two students in each category. Data were collected through written tests, think-aloud, and interviews, and were analyzed through data reduction, data display, and conclusion drawing. The results showed that students in the high category demonstrated complete metacognitive ability in the aspects of planning, monitoring, and evaluating. Students in the medium category demonstrated the three aspects; however, their monitoring was not yet optimal, especially in adjusting problem-solving steps when errors were found. Students in the low category were able to planning and monitoring the solution process in a simple way; however, their evaluating ability was not yet optimal, particularly in rechecking the answers obtained.